Constraints on perfect fluid and scalar field dark energy models from future redshift surveys - Amendola, Luca; Quercellini, Claudia; Giallongo, Emanuele (Monthly notices of the Royal Astronomical Society, 2005)
We discuss the constraints that future photometric and spectroscopic redshift surveys can put on dark energy through the baryon oscillations of the power spectrum. We model the dark energy either with a perfect fluid or a scalar field and take into account the information contained in the linear growth function. We show that the growth function helps to break the degeneracy in the dark energy parameters and reduce the errors on w0, w1 roughly by 30 per cent, making more appealing multicolour surveys based on photometric redshifts. We find that a 200-deg2 spectroscopic survey reaching z≈ 3 can constrain w0, w1 to within Δw0 = 0.21, Δw1 = 0.26, to Δw0 = 0.39, Δw1 = 0.54 using photometric redshifts with an absolute uncertainty of 0.02, and to Δw0 = 0.43, Δw1 = 0.66 with an uncertainty of 0.04. In the scalar field case, we show that the slope n of the inverse power-law potential for dark energy can be constrained to Δn = 0.26 (spectroscopic redshifts) or Δn = 0.40 (photometric redshifts), i.e. better than with future ground-based supernovae surveys or cosmic microwave background data.